Investigating pollination strategies in disturbed habitats: the case of the narrow-endemic toadflax Linaria tonzigii (Plantaginaceae) on mountain screes - Paolo Biella; Asma Akter; Antonio Jesús Muñoz-Pajares; Germano Federici; Andrea Galimberti; Jana Jersáková; Massimo Labra; Federico Mangili; Nicola Tommasi; Luca Mangili (Plant Ecology, 2021)
Plant mating systems may reflect an adaptation to a habitat type, with self-pollination being potentially common in unstable and disturbed conditions. We investigated the reproductive ecology of an Alpine, narrow-range toadflax, Linaria tonzigii Lona (Plantaginaceae), occurring in steep and dynamic mountain screes. We explored self-compatibility and spontaneous autogamy, seed viability, daily nectar production, pollinator behaviour and pollen transfer in wild populations, using hand pollination treatments, quantification of nectar volume, viability Tetrazolium assay, active pollinator sampling and video recordings, and UV-bright dust for pollen substitution. After ex novo sequencing of several genetic regions of L. tonzigii , we performed a multi-marker phylogenetic analysis of 140 Linaria species and tracked the occurrence of the self-compatibility trait. Our results showed that this species is self-compatible, pollinated mostly via spontaneous autogamy and pollinator-mediated geitonogamy, and self-pollinated seeds are as viable as cross-pollinated ones. Selfing could be due to pollinator rarity because, despite the studied species providing a high nectar volume, wild bees, moths and small beetles infrequently visited its flowers in the sparsely vegetated scree slopes. In addition, a preliminary survey showed a low genetic haplotype diversity in the study plant. Moreover, the phylogeny shows that self-compatibility is scattered in the tree, suggesting the adaptive nature of this reproductive trait in the genus Linaria . This study supports for theories that high prevalence of selfing is an adaptation to environments unfavourable for cross-pollination, and particularly where pollinators are rare, such as in perturbed, poorly vegetated high-elevation habitats.